Progress in immunoregulatory mechanisms during distraction osteogenesis - Huang, Shiyu; Zeng, Aoran; Yin, Qing; Yang, Qiming; Zou, Bing; He, Meiying; Wang, Juehan; Pan, Qi (Frontiers in Bioengineering and Biotechnology, 2025)
Distraction osteogenesis (DO) is an endogenous bone tissue engineering technique that harnesses the regenerative potential of bone and has been widely applied in limb lengthening, bone defect repair, and craniofacial reconstruction. The DO procedure consists of three distinct phases: the latency phase, the distraction phase, and the consolidation phase, each characterized by unique biological processes. In recent years, increasing attention has been directed toward the role of the immune system during DO. Emerging evidence demonstrates that immune cells exhibit dynamic and temporally regulated changes throughout the different phases of DO. Moreover, immunomodulatory clinical interventions—such as the regulation of immune-related factors and the application of bioactive materials—are becoming promising strategies for optimizing DO outcomes. This review aims to summarize the temporal characteristics of immune regulation during DO, elucidate the functions and regulatory mechanisms of various immune cells involved, and explore the potential of immunomodulatory biomaterials, thereby providing novel insights for improving DO-based therapies.